La inmigración italiana en Santa Fe: español e italiano en contacto. Motivaciones, metodologías y primeros resultados de un proyecto internacional (El Hilo de la Fabula, 2019)
Italian immigration in and around Santa Fe presents a phenomenon of contact and linguistic hybridization between the local Spanish and the Italian and the Italian dialects of immigrants —a field of study that to date remains open for study. This contribution outlines the motivations, methodologies and results of the first stage of work within the framework of an international project between scholars from the Universidad Nacional del Litoral and the University ofMelbourne, Australia, aimed at describing and analyzing the characteristics and consequences of contact.
Keywords: Italian immigration; linguistic contact; Italian and Spanish; Argentina